DEVELOPMENT OF A STRATEGIC MODEL FOR NEW STUDENT DORMITORY MANAGEMENT - Nurjaman, Buldan; Al Kattani, Abdul Hayyie; Rosyadi, A. Rahmat (Al-Mubin, 2025)
The phenomenon of many new students who do not feel at home, have difficulty adapting, and choose to leave the pesantren is a serious problem faced by many pesantren This is due to the weak dormitory management system that has not run strategically and directionally. In fact, the dormitory is a center for character development and habituation of Islamic values for students. Therefore, it is necessary to develop a dormitory strategic management model that is able to respond comprehensively to the adaptation needs of new students. This research aims to develop a strategic model of new student dormitory management at the MTs level in Islamic boarding schools, in order to optimize the adaptation process of new students in the pesantren environment. This research uses the Research and Development (R&D) approach with the ADDIE model and the strategic management theory approach of Fred R. David, which includes the stages of strategy formulation, strategy implementation, and strategy evaluation. The research also integrates Islamic values from the thought of Imam Al-Ghazali and Ibn Khaldun to strengthen the spiritual and moral dimensions in the management of the dormitory. The results of this research produce a strategic model that is not only operational, but also rooted in Islamic educational values, so that it can be a reference for Islamic boarding school institutions in improving the quality of dormitory management, especially in assisting new students to live the early life in Islamic boarding schools